2010
DOI: 10.1590/s1808-86942010000500003
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência da síndrome da apneia obstrutiva do sono (SAOS) em crianças respiradoras orais

Abstract: It is well known that mouth breathing is associated with adenotonsillar hypertrophy -which is the main cause of obstructive sleep apnea among children. Despite the importance of this matter, there are only a handful of studies showing the relationship between OSAS and mouth breathing.Aim: to determine the prevalence of obstructive sleep disorders in mouth breathing children and study its correlation with otorhinolaryngological findings. Study design: Retrospective cohort study.Method: Data analysis from 248 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Moreover, the number of cases of respiratory complications related to allergic rhinitis and obstructive sleep apnea is increasing, especially during preadolescence and adolescence growth periods (Abreu et al, 2008; Juliano et al, 2009; Izu et al, 2010). The earlier the nasal obstruction develops, the earlier associated alterations can occur, not only in the respiratory system, but also in the whole body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the number of cases of respiratory complications related to allergic rhinitis and obstructive sleep apnea is increasing, especially during preadolescence and adolescence growth periods (Abreu et al, 2008; Juliano et al, 2009; Izu et al, 2010). The earlier the nasal obstruction develops, the earlier associated alterations can occur, not only in the respiratory system, but also in the whole body.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have elucidated that nasal obstruction induces a significant reduction in the vertical development of the nasomaxillary complex and skull base along the longitudinal axis (Scarano et al, 1998). It also results in a significant reduction in the growth of the masseter and the anterior digastric (Dig) muscle (Gelhaye et al, 2006; Izu et al, 2010). With regard to masticatory function (Hsu and Yamaguchi, 2012; Ikenaga et al, 2013), previous studies have shown that oral breathing reduces masseter muscle activity (Ferla et al, 2008), and increases suprahyoid muscle activity and hypotonia of the lips and buccinator muscle (Valera et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some factors that may justify this fact could also be investigated, such as the presence of a higher incidence of upper airway infections (28) and hypertrophic tonsils and adenoids in this age group (29) , which can aggravate respiratory symptoms (30) . Furthermore, the presence in the children's group of a caregiver or other person responsible for information about symptoms favors a detailed account of respiratory signs and symptoms during sleep, which is not available in the case of many young adults.…”
Section: Discussionmentioning
confidence: 99%
“…The adenoids, also known as pharyngeal or nasopharyngeal tonsils, are important components of the Waldeyer's ring (1). Adenoid hypertrophy (AH) is enlargement of the adenoids; it is frequent in the pediatric population and can cause symptoms such as mouth breathing, nasal obstruction, hyponasal speech, snoring, and sleepdisordered breathing (SDB) (2)(3)(4). The exact mechanisms underlying AH remain extremely poorly understood, but it has been assumed that recurrent or chronic inflammation plays a role (5).…”
Section: Introductionmentioning
confidence: 99%